DESIGNING AND ADAPTING MATERIALS FOR DIFFERENTIATED INSTRUCTION IN ENGLISH LANGUAGE CLASSROOMS: A LITERATURE REVIEW - Andrean, Chandra (Universitas PGRI Sumatera Barat, 2023)
This qualitative study explores the process of designing and adapting materials for differentiated instruction in English language classrooms. The study aims to identify the factors that influence this process, the strategies that teachers use, and the challenges and opportunities they face. The study finds that the process of designing and adapting materials for differentiated instruction is complex and multifaceted, and is influenced by factors such as the needs and characteristics of learners, the curriculum and assessment requirements, and the available resources and technologies. Teachers use a variety of strategies to design and adapt materials, including modifying existing materials, creating new materials, and using digital tools and resources. The findings can inform future research and practice in the field of English language teaching, and contribute to the development of effective and inclusive approaches to language learning and teaching.